Analisis Koefisien Korelasi Peak Ground Acceleration Dengan Metode Oliviera dan Shakemap BMKG, Studi Kasus Gempabumi Bantul 16 Januari 2022 - Salma Aprillina Kurniawan; Efita Pratiwi Adi; Wuri Handayani; Setyoajie Prayoedhie (Jurnal Stasiun Geofisika Sleman, 2023)
The analysis of the coefficient correlation of peak ground acceleration (PGA) using Oliviera Method and BMKG’s shakemap based on case study of the earthquake in Bantul January, 16th 2022. This study aims to determine of peak ground acceleration value and to determine coefficient correlation value of peak ground acceleration and BMKG’s shakemap. The earthquake data used is the earthquake data on January 16th 2022 in Bantul. Based on this data, PGA value when using the Oliviera method is 10.109 gals or 0.0101 g. Meanwhile, PGA value of BMKG’s shakemap is 70.28543 gals or 0.070285 g. The result of the coefficient correlation between PGA value uses Oliviera method with PGA value of BMKG’s shakemap is 0.9958. It shows the relationship between the two values has a positive curve and shows a strong relationship.